2011
DOI: 10.1037/a0021238
|View full text |Cite
|
Sign up to set email alerts
|

Trait emotions and affective modulation of the startle eyeblink: On the unique relationship of trait anger.

Abstract: We examined relationships among individual differences in trait emotions and the emotion-modulated startle-eyeblink response. In particular, we examined the extent to which trait anger, which is negative in valence, would be associated with a pattern of approach motivation in startle eyeblink responses to appetitive stimuli. Self-reported trait emotions were compared with emotion-modulated startle eyeblink responses to auditory probes during appetitive, aversive, and neutral pictures. Results revealed that tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 34 publications
(45 reference statements)
3
18
0
Order By: Relevance
“…A recent study examined trait anger in relation to startle eyeblink responses (Amodio & Harmon‐Jones, ) and found that trait anger, as well as the other approach‐oriented emotions such as interest and enjoyment, were associated with startle eyeblink inhibition in response to probes during arousing positive stimuli.…”
Section: Methodology Of Examining the Acoustic Startle Eyeblinkmentioning
confidence: 99%
“…A recent study examined trait anger in relation to startle eyeblink responses (Amodio & Harmon‐Jones, ) and found that trait anger, as well as the other approach‐oriented emotions such as interest and enjoyment, were associated with startle eyeblink inhibition in response to probes during arousing positive stimuli.…”
Section: Methodology Of Examining the Acoustic Startle Eyeblinkmentioning
confidence: 99%
“…Startle probes elicit larger eye blinks while participants view arousing aversive images (compared to neutral, nonarousing images), but smaller eye blinks while viewing arousing appetitive images (compared to neutral, nonarousing images; e.g., Lang et al, ). This differentiation in startle eye‐blink responses as a function of aversive versus appetitive stimuli has been used in prior research to elucidate a person's emotive state (e.g., Amodio & Harmon‐Jones, ; Caseras et al, ; Lang, ).…”
Section: Studymentioning
confidence: 99%
“…This is usually a short burst of white noise and is referred to as an auditory startle probe. The magnitude of the startle response is modulated by emotional valence, and is considered a well-established psychophysiological measure capable of distinguishing between the approach-avoidance dichotomy of emotions [10], [11]. With presentation of pleasant stimuli triggering approach motivation, the startle magnitude in response to an auditory startle probe is reduced relative to a neutral emotional state, whereas it is increased when aversive stimuli related to avoidance motivation are presented.…”
Section: Introductionmentioning
confidence: 99%